Proceedings of the Joint 15th Linguistic Annotation Workshop (LAW) and 3rd Designing Meaning Representations (DMR) Workshop 2021
DOI: 10.18653/v1/2021.law-1.6
|View full text |Cite
|
Sign up to set email alerts
|

Classifying Divergences in Cross-lingual AMR Pairs

Abstract: Translation divergences are varied and widespread, challenging approaches that rely on parallel text. To annotate translation divergences, we propose a schema grounded in the Abstract Meaning Representation (AMR), a sentence-level semantic framework instantiated for a number of languages. By comparing parallel AMR graphs, we can identify specific points of divergence. Each divergence is labeled with both a type and a cause. We release a small corpus of annotated English-Spanish data, and analyze the annotation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Recent work classified these AMRs via AMR structural divergence schema (Wein and Schneider, 2021) (mentioned in §2). (Wein and Schneider, 2021) In table 3, we measure the ability of our pipeline system and the and Carpuat, 2020) system to detect semantic divergences at a stricter level, as picked up by the AMR divergence schema.…”
Section: Results On Gold English-french Amr Pairsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work classified these AMRs via AMR structural divergence schema (Wein and Schneider, 2021) (mentioned in §2). (Wein and Schneider, 2021) In table 3, we measure the ability of our pipeline system and the and Carpuat, 2020) system to detect semantic divergences at a stricter level, as picked up by the AMR divergence schema.…”
Section: Results On Gold English-french Amr Pairsmentioning
confidence: 99%
“…Recent work has investigated the differences in cross-lingual (English-Spanish) AMR pairs within the framework of translation divergences (Wein and Schneider, 2021). Specifically, this work developed an annotation schema to classify the types and causes of differences between cross-lingual AMR pairs.…”
Section: Background On Semantic Divergencementioning
confidence: 99%
“…A second limitation of the previous Spanish AMR annotation was the limited amount of change to the English AMR guidelines to incorporate Spanish linguistic phenomena. Recent work has assessed various differences between Spanish and English annotations of the existing Spanish AMR adaptation, classifying the type and cause of the identified differences (Wein and Schneider, 2021).…”
Section: Prior Work Adapting Amr To Spanishmentioning
confidence: 99%
“…to adequately capture semantic phenomena in Spanish, they indicated that accurate representation could be accomplished by adding specific roles and constructions. For example, the English and Spanish AMRs in figure 1, which annotate parallel sentences, have two syntactic divergences due to inherent differences between the languages (Wein and Schneider, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, it has to face two limitations (at least): relying on the translation quality, which is not the same for all languages, and the possible domain-level divergence between the translated and the gold corpora, which can prevent leveraging all its potential. Concerning AMR, we also can suffer from some structural divergences in the translated AMR graphs (Sobrevilla Cabezudo et al, 2019;Wein and Schneider, 2021) as, originally, AMR is highly biased to English (Banarescu et al, 2013).…”
mentioning
confidence: 99%